How do Kinetochores CLASP Dynamic Microtubules? - Maiato, H (2003)
Maintenance of genetic stability during cell division requires binding of chromosomes to the mitotic spindle, a process that involves attachment of spindle microtubules to kinetochores. This enables chromosomes to move to the metaphase plate, to satisfy the spindle checkpoint and finally to segregate during anaphase. Recent studies on the function MAST in Drosophila and its human homologue CLASP1, have revealed that these microtubule-associated proteins play an essential role for the kinetochore-microtubule interaction. CLASP1 localizes to the plus ends of growing microtubules and to the most external kinetochore domain. Depletion of CLASP1 causes abnormal chromosome congression, collapse of the mitotic spindle and attachment of kinetochores to very short microtubules that do not show dynamic behavior. These results suggest that CLASP1 is required at kinetochores to regulate the dynamic behavior of attached microtubules.